2019
DOI: 10.1200/jco.2019.37.15_suppl.11504
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine (OLN) versus aprepitant (APR) in patients receiving high-emetogenic chemotherapy: Final results of randomized phase II trial.

Abstract: 11504 Background: Management of chemotherapy-induced nausea and vomiting (CINV) remains challenging. OLN might provide several benefits over APR which is current standard of care – particularly in terms of nausea control and cost effectiveness. However, sedation associated with recommended doses of olanzapine precludes its wide use in oncology practice. Methods: This was randomized phase II single center study aimed to compare OLN and APR in CINV prophylaxis. Key inclusion criteria were: chemo- and radio-ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
8
2
Order By: Relevance
“…NCCN panel recommends an olanzapine-containing three-drug regimen with palanosetron and dexamethasone, since; there was no large clinical trial available for the other 5-HT3 antagonists (2). However, several phase II trials also supported the superiority efficacy in terms of nausea control by olanzapine 10 mg in combination with ondansetron plus dexamethasone when compared to the standard dose of aprepitant in combination (5,6). Our study also demonstrated the efficacy of olanzapine 10 mg in the three-drug regimen with ondansetron and dexamethasone in terms of the nausea control and the complete response rate in acute phase (7).…”
supporting
confidence: 75%
“…NCCN panel recommends an olanzapine-containing three-drug regimen with palanosetron and dexamethasone, since; there was no large clinical trial available for the other 5-HT3 antagonists (2). However, several phase II trials also supported the superiority efficacy in terms of nausea control by olanzapine 10 mg in combination with ondansetron plus dexamethasone when compared to the standard dose of aprepitant in combination (5,6). Our study also demonstrated the efficacy of olanzapine 10 mg in the three-drug regimen with ondansetron and dexamethasone in terms of the nausea control and the complete response rate in acute phase (7).…”
supporting
confidence: 75%
“…Three studies reported on olanzapine for the rescue of breakthrough CINV [ 42 44 ]; 22 studies reported on olanzapine in the prophylactic setting [ 45 66 ]. Only seven studies (one reporting on rescue of breakthrough CINV, and six reporting on prophylactic CINV) had no corresponding full-text articles [ 42 , 48 , 53 , 55 , 56 , 60 , 61 ]. One study reported on olanzapine for children [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the adult prophylactic studies, 15 reported exclusively on HEC patients [ 46 , 49 52 , 55 , 56 , 58 , 60 66 ], three exclusively on MEC patients [ 53 , 57 , 59 ], and three on a patient population that consists of both HEC and MEC patients [ 45 , 47 , 54 ]. Eight studies compared olanzapine to a double-blind placebo-controlled regimen [ 47 , 52 , 59 , 62 66 ] and thirteen used an opened controlled study design—nine studies used a control arm with antiemetics different from the antiemetics in the investigational (olanzapine-containing) arm [ 46 , 49 , 51 , 53 , 55 , 56 , 58 , 60 , 61 ] and four used a control arm with the same antiemetics as in the investigational (olanzapine-containing) arm except for olanzapine [ 45 , 50 , 54 , 57 ]. 17 adult prophylactic studies used 10 mg doses of olanzapine [ 45 , 46 , 49 59 , 61 , 62 , 65 , 66 ], and 3 studies used 5 mg [ 47 , 60 , 63 ]; 1 used a mix of 5 mg and 10 mg [ 64 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently a paucity of data reporting on olanzapine administered at the 5mg dose. Only 3 studies by Hasimoto et al 9 , Mizukami et al 10 and Rumyantsev et al 11 have compared 5mg to placebo, while Ishimoto et al 12 compared 5-mg to 10-mg and to placebo. In contrast, 17 studies have reported on olanzapine in the 10mg setting.…”
Section: Introductionmentioning
confidence: 99%